Cryo-EM structures of the small-conductance Ca2+-activated KCa2.2 channel - Young-Woo Nam; Dohyun Im; Ana Santa Cruz Garcia; Marios L. Tringides; Hai Minh Nguyen; Yan Liu; Razan Orfali; Alena Ramanishka; Grigore Pintilie; Chih-Chia Su; Meng Cui; Diomedes E. Logothetis; et al. (Nature Communications)
Abstract Small-conductance Ca2+-activated K+ (KCa2.1-KCa2.3) channels modulate neuronal and cardiac excitability. We report cryo-electron microscopy structures of the KCa2.2 channel in complex with calmodulin and Ca2+, alone or bound to two small molecule inhibitors, at 3.18, 3.50, 2.99 and 2.97 angstrom resolution, respectively. Extracellular S3-S4 loops in β-hairpin configuration form an outer canopy over the pore with an aromatic box at the canopy’s center. Each S3-S4 β-hairpin is tethered to the selectivity filter in the neighboring subunit by inter-subunit hydrogen bonds. This hydrogen bond network flips the aromatic residue (Tyr362) in the filter’s GYG signature by 180°, causing the outer selectivity filter to widen and water to enter the filter. Disruption of the tether by a mutation narrows the outer selectivity filter, realigns Tyr362 to the position seen in other K+ channels, and significantly increases unitary conductance. UCL1684, a mimetic of the bee venom peptide apamin, sits atop the canopy and occludes the opening in the aromatic box. AP14145, an analogue of a therapeutic for atrial fibrillation, binds in the central cavity below the selectivity filter and induces closure of the inner gate. These structures provide a basis for understanding the small unitary conductance and pharmacology of KCa2.x channels.